ANALISIS ANTIVIRUS SMADAV UNTUK MANGATASI SERANGAN VIRUS LOKAL PADA KOMPUTER - Febriando Tambunan; Tio Suhada; Ali Ibrahim (Annual Research Seminar (ARS), 2017)
ABSTRACTComputer viruses are made intentionally by someone with a variety of purposes. Computer viruses have the ability to self-duplicate and even manipulate. To prevent the attack then created antivirus software that is useful to overcome the virus attacks. Installing antivirus on a computer is a hightly recommended thing every computer user. Now many people are creating various types of antivirus, such as Smadav. The ease given by smadav in installing its software is very helpful in the use of this antivirus. We can directly use it because this antivirus is free and can be used in all computer operating systemKeyword: Computer viruses, Antivirus, Smadav